TEACHING ENGLISH TO PRESCHOOLERS BASED ON VOCABULARY EXERCISES - Subhonova Anora Akmal qizi (Western European Studies, 2024)
The article examines novel approaches and tactics employed in the instruction of English to young children in preschool settings, with a specific focus on vocabulary enhancement exercises. The pedagogical approach places significant emphasis on the utilization of a diverse range of tools and techniques, including but not limited to visual aids, interactive games, storytelling, songs and rhymes, hands-on activities, and exercises that include technology. The primary objective of these strategies is to actively include and capture young learners, so facilitating the enhancement of their language skills.
Keywords: enhancement; learners; facilitating